Assessment of root morphology and canal configuration of maxillary premolars in a Saudi subpopulation: a cone-beam computed tomographic study - Saad M. Al‑Zubaidi; Moazzy I. Almansour; Nada N. Al Mansour; Ahad S. Alshammari; Ahad F. Alshammari; Yazeed S. Altamimi; Ahmed A. Madfa (BMC, 2021)
Abstract Background The objective of this study was to use CBCT to look into the root canal morphology of maxillary premolars in a Saudi Arabian subpopulation and associate the results to existing canal morphology classifications. Methods The sample size for this analysis was 500 right and left untreated maxillary first and second premolars with fully formed roots from 250 Saudi residents (125 male and 125 female). The following observations were made using CBCT on the teeth related: (1) The number and morphology of roots; (2) The canal morphology for each root according to Vertucci's classification. The frequency and similarities between the right and left sides, as well as between females and males, were studied. The Chi-square test was used to assess the results. Results Of the 500 maxillary first premolars studied, 199 teeth had one root (39.8%), whilst 293 (58.6%) were two-rooted. Three-rooted maxillary first premolars were found in 8 (1.6%). For maxillary second premolars, 416 premolars had one root (83.2%), whilst 79 (15.8%) had two roots and the rest 5 (1.0%) were three roots. There were significant differences of number of root were found between groups (p > 0.05). For maxillary first premolar, Type IV was the most frequent, accounting for 57.8% of the sample (n = 289), followed by type II (32.8%, n = 164). For maxillary second premolar, Type I was mainly occurrence 302 (60.4%), followed by Type II (16.4%, n = 82). Conclusions The majority of maxillary first premolars had two roots and two root canals, while one root and one root canal was the most common anatomical configuration for maxillary second premolars. Additional canal forms do occur on occasion, and clinicians should pay close attention to them.